THE ROLE OF THE PRIMARY CARE PHYSICIAN IN THE PREVENTION OF NON-COMMUNICABLE DISEASES - A REVIEW - Martyna Kadłubańska; Natalia Piasecka; Karolina Szpilczyńska; Natalia Miara; Joanna Strzyż; Dorota Szydłowska; Aleksandra Baraniecka; Melania Majewska (International Journal of Innovative Technologies in Social Science, 2026)
Non-communicable diseases represent one of the greatest challenges for modern healthcare systems and are the leading cause of premature mortality worldwide. Effective prevention of these conditions requires integrated actions implemented at the primary healthcare level, which plays a key role in both primary and secondary prevention. The aim of this article was to present the role of the primary care physician in preventing non-communicable diseases, with particular emphasis on new care models, interdisciplinary teams, digital tools, and systemic barriers that limit the effectiveness of preventive measures. This work is a literature review. Publications in the field of public health and family medicine concerning the prevention of non-communicable diseases, the functioning of primary care, care integration, digitalization, and healthcare system preparedness were analysed. Selected sources were subjected to critical qualitative analysis, and the data obtained were synthesized thematically. The review results indicate that primary care forms the foundation for effective prevention of non-communicable diseases due to its capacity for early identification of risk factors, conducting screening tests, and long-term collaboration with patients. At the same time, the growing importance of interdisciplinary teams and digital tools, which complement the traditional care model, was emphasized. However, significant limitations remain in the form of organizational, staffing, and systemic barriers. The conclusions highlight the need for further development of integrated care models and research on effective strategies for implementing prevention in primary care.